ANALISIS PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA PEGAWAI PADA BPPKAD KABUPATEN PONOROGO DENGAN PERFORMANCE APPRAISAL SEBAGAI VARIABEL MODERASI - Aviantoro, Dhutarso; Suseno, Y. Djoko; Widodo, Untung Sri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The aims of the research is to examine the influence of giving reward and punishment at the Regional Finacial and Asset Management Revenue Agency of Ponorogo Regency. Meanwhile, the research is applicable for Regional Finacial and Asset Management Revenue Agency of Ponorogo Regency to increase the staff performance by giving reward and punishment. To trigger the performance of employees at the Regional Finacial and Asset Management Revenue Agency of Ponorogo Regency, reward or recognition is required for accomplishments but instead should be given punishment for violations or omissions. Performance Appraisal at the other side as the moderation variable can affect the reward and punishment that given to the emplyoyees.Basic theory underlying this study is a Reinforcement Theory of Motivation by Skinner with a focus on reward, punishment and performance.The analysis tool used is multiple linear regression.Research shows that reward has a positive and significant effect on the performance, Punishment has a positive and significant impact on the performance, Performance appraisal has a positive and significant impact on the performance, Performance appraisal has a positive effect but has not significant impact in the role of reward to the performance and Performance appraisal has a positive effect but has not significant impact in the role of punishment to the performance.